The challenges facing the Iraqi culture and development in a time of digital culture - Ibrahim, Thikra Abd Almonem (Al-Adab Journal, 2020)
The research aims to understand the challenges facing culture and development in Iraqi society means of communication in the rationalization of development awareness of young people in a world increasingly faithful to the importance of digital culture. The theme of the importance and research to take day after day is increasing in our society of increasing Attenting digital culture on our , if there is no conscious enough to counter the negative ones aspects , and the introduction of the positive aspects that should be able to interact with them to enter into the era of evolution and foot ,In this regard, it should be aware that Iraqi society is undergoing a historic era of critical , which crumbled risk from every direction , there is a huge internal problems related to the economy , culture, education , values ​​and crises youth external risks looming and lurking out at all levels have overlapped internal problems with external problems , but that a large part of the internal problems date back to external challenges began to mount intensively with the old colonialism and the looting of its wealth on the one hand ideological reasons, on the other hand, Even if the world was divided on the two poles main Iraq signed like the rest of the Arab countries under the influence of Aediologithma and their culture even if the socialist pole collapse dominated capitalist pole on the world has practiced the politics of globalization in various forms on the ground, the people, so that has become the cultural identity is threatened with the flow of the culture of globalization and pursuing social its crises and political and economic, with the rising tide of globalization, and the growing use of modern means of communication by the new generations, exposed to the culture in which fragmentation swerved manifestations of the Assembly to the values ​​of individual values ​​with the emergence of youth culture distasteful regimes affected by the rapid flow of technical culture, So there is a sense of deep concern over national identity and the challenge of the division, and increasingly dangerous with the introduction of political projects in the Arab arena , including the new Middle East project, which makes Israel a key partner which also was the last invitations, French call to find a farm north of the Mediterranean countries and the countries of southern Europe attempt to marginalize and fragment the entire area . So the research problem lies in the impending Iraqi cultural identity risk , especially youth culture in a dual world in its arguments , it is let to democracy , human rights and respect for each other and exercise at the same time marginalization and blur the identity of the peoples of the free and the peoples of the Arab region policy .The research methodology shall be Ballaatmad on the two tools Aalbges anthropological ( disassembly and integration ), which shows the use in the study of culture and personality , especially in the field of cultural anthropology